Are they even following us?: Using market research data to understand students' social media preferences. Issue 8 (11th November 2019) - Polger, Mark Aaron; Sich, Dan
Abstract : Purpose: The purpose of this paper is the exploration of students' preferred social media (SM) tools for receiving information about their academic library. The authors administered a questionnaire at their prospective institutions: the College of Staten Island (CSI), City University of New York, USA and the University of Western Ontario (UWO) in London, Ontario, Canada. The authors examine students' preferences for various SM tools, and analyzed the types of information students expect from the library's SM accounts. The authors argue that the library's SM postings should be curated based on market research that provides a better understanding of the target audience. Design/methodology/approach: The authors explore the SM preferences of students at their prospective institutions. The authors examine the SM channels students visit and the types of SM content they wish to seek out. The authors ran the authors' study from September 1 through December 31, 2016. The authors used convenience sampling and a printed questionnaire to collect data from students in information literacy instruction sessions ( n =633 at CSI, n =602 at UWO). Findings: The authors found that more students (at both institutions) used Facebook and YouTube, as compared with other SM platforms. If they viewed their library's SM accounts, students from both institutions preferred to read about news and current events, followed by announcements about new library services. Practical implications: The authors illustrate that conducting market research helps SM managers understand their target audience. Market research is the key to successful SM management. It also helps in the development of a marketing plan and provides insights on students' preferences regarding SM content. Originality/value: This study compares students' SM preferences across two academic institutions from two countries, the USA and Canada. The authors wished to investigate the similarities and differences among these students' preferences.